Meningkatkan kemampuan pengambilan keputusan karir siswa melalui teknik scaling - Tusmiati, Tusmiati; Aminudin, Djoni; Ilahi, Fauzi Nur (Orien: Cakrawala Ilmiah Mahasiswa, 2023)
the study aims to analyze and test the correctness of hypotheses regarding Improvement between career decisions with scaling techniques. This research is a preexperimental design research with the type of one group pretest-posttest design. Samples were taken by purposive sampling technique. The population is grade XI students of SMK Negeri 9 Bekasi City with a sample of 72 students. The research instrument used was a career decision questionnaire of 30 items that had been tested for normality with a magnitude of 0.523 > 0.05. and homogeneity test with GIS 0.010, > 0.05. The results of hypothesis testing obtained the following conclusion: tcalculate > ttable (- 23.556 > -1.666) or sig. 0,000 < 0.05 then Ho is rejected and Ha is accepted. Ha accepted means that there is an increase in students' career decision making ability at SMK Negeri 9 Bekasi City.